Political Communication and Gender: An Analysis of Public’s Perceptions Toward the Election of the 2017 Mayoral Candidates of Banda Aceh - Nur Anisah; Zakirah Azman; Rahmat Saleh; Lia Monita; Nadia Muharman; Maini Sartika (UIR Press, 2022)
This research attempted to describe the public's perception toward political communication ofcertain gender in winning the mayoral election of Banda Aceh in 2017 and to find outpeople's perceptions on whether gender is able to influence the candidacy in winning themayoral election of Banda Aceh in 2017. This research was conducted by using qualitativemethod and took place in Banda Aceh. The process of retrieving data and information of theresearch is obtained from the review of literature. This research employed structured-interview on expert informants from the Independent Election Commission, the Head ofIslamic Shari'a Office of Banda Aceh and the voting community (male and female) selectedby using purposive sampling. The theory used in this research is the theory of socialcognition, a learning theory explaining the patterns of behavior. This theory was developedby Albert Bandura since 1960 and emphasized the tendency to imitate or emulate whatpeople see through the media or other people. There are interrelationships betweenindividuals, environment and behavior. In this case, the political communication carried outby the two mayor candidates of Banda Aceh stemmed a new problem since one of thecandidates was female. As the result, this issue triggered a controversy in the community interms of contradicting the teachings of Islamic Shari'a among candidates and within thecommunity regarding gender. In terms of political participation, women have been givenspecial proportion in both management of political parties and legislative candidacy (30%).Meanwhile, this arrangement is still not well-considered because there are no strict sanctionsfor political parties. In respect of sociological aspects, there are still many serious problems, starting from women's interest which is still low in the political sphere as well as theproblems of gender bias experienced by women. Furthermore, the urgency of women'srepresentation in the political sphere is hampered due to negative stereotypes towards womenand the level of patriarchal knowledge which still sticks on people's lives.